The Hindu nationalist movement in India - Jaffrelot, Christophe (Viking, 1996)
Although the peaceful, inward-looking doctrine of the Hindu religion hardly seems to lend itself to ethnic nationalism, a phenomenal surge of militant Hinduism has taken place over the last ten years in India, precipitating a wave of Hindu-Muslim riots in India in the late 1980s and early 1990s. Indeed, the electoral success of the Hindu nationalist Bharatiya Janata Party (BJP) has proven beyond a doubt that these fundamentalists now pose a significant threat to India's secular government.